Solanum membranisepalum (Solanaceae): A new name for the Flora of China - Zhang, Libing; Lu, Ngan Thi (Phytotaxa, 2014)
Solanum membranisepalum Li Bing Zhang & Ngan T. Lu is proposed as a replacement name for the later homonym S. griffithii (Prain) C.Y. Wu & S.C. Huang